2020
DOI: 10.18549/pharmpract.2020.1.1660
|View full text |Cite
|
Sign up to set email alerts
|

Community pharmacists’ recommendations for natural products for stress in Melbourne, Australia: a simulated patient study

Abstract: Background: Community pharmacists are often the first health professional approached to provide treatment for health issues, including the important mental health challenge, stress. Over-the-counter products for stress almost always are complementary and alternative medicines (CAM) and in Australia no protocol exists for their recommendation and sale in community pharmacies. Objective: To assess the quality and relevance of community pharmacists' information gathering (questioning), counselling and product sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 17 publications
(13 reference statements)
0
6
0
3
Order By: Relevance
“… 7 A simulated patient study conducted in Australian pharmacies showed numerous shortcomings in their practices regarding CAM recommendation and dispensing, including advising use of products with unproven efficacy and safety. 13 Another study, by McKee et al , also revealed that pharmacists’ decision on over-the-counter (OTC) drugs was not influenced by evidence. 14 Moreover, the authors concluded that if community pharmacists aim to be considered as scientific health care professionals, they should discuss evidence with their patients.…”
Section: Discussionmentioning
confidence: 99%
“… 7 A simulated patient study conducted in Australian pharmacies showed numerous shortcomings in their practices regarding CAM recommendation and dispensing, including advising use of products with unproven efficacy and safety. 13 Another study, by McKee et al , also revealed that pharmacists’ decision on over-the-counter (OTC) drugs was not influenced by evidence. 14 Moreover, the authors concluded that if community pharmacists aim to be considered as scientific health care professionals, they should discuss evidence with their patients.…”
Section: Discussionmentioning
confidence: 99%
“… 31 A study conducted in Iran identified low-quality counseling practice on vitamin supplementation and suggests that it is related to insufficient information gathering, inadequate knowledge and deficiencies in the communication skills of professionals. 32 Note that all these studies were conducted to check the performance in community pharmacies and their results showed also a poor scenario. 36 …”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found that counseling on forgetting to take the medication and contraindications of the drugs are the least likely to be communicated to patients. 29,32 In the study of Paravattil, Kheir and Yousif (2017), the drug allergies, the offer of pharmaceutical follow-up, and the verification of understanding of the information provided to the patient were not met by any of the pharmacists and only 6.5% of the participants correctly explained all the steps in device management. 29 Between 10 and 20% of our pharmacists recommended non-pharmacological care measures, such as regular physical activity, reduced salt intake, or reduce exposure to allergens, among others.…”
Section: 21mentioning
confidence: 99%
See 2 more Smart Citations